Kết quả bước đầu nghiên cứu hướng và phạm vi phân tỏa vật liệu phù sa Sông Hồng ở vùng biển ven bờ Vịnh Bắc Bộ - Hồng, Lê Xuân; Vinh, Phạm Ngọc (Vietnam Journal of Earth Sciences, 2002)
Preliminary results of studying the movement direction of the Red river's sediments and their effect domain in the coastal zone of the gulf of Tonkin